HELPING YOUNG LEARNERS TO LEARN AUDIO DISCRIMINATION BY USING FLASHCARDS - Yansyah, Yansyah (English Department of Faculty of Tarbiyah and Teachers Training, 2015)
The ability of young learners to grasp and to imitate what they hear is one of potential opportunities that should be taken into account by EYL teachers. They can use this advantage to facilitate them to acquire a good pronunciation since their earlier age. This article then tries to propose a classroom idea on how to help young learners learn audio discrimination by using flashcards. Audio discrimination is the ability to recognize the similarities and the differences among different sounds. This ability is very important to be developed especially for the teaching of reading since learners need to discriminate between sounds associated with different letters. Flashcards are considered as appropriate media because of its practicality to be used in the classroom and its economical reason. The detail of teaching procedure will be listed in pre-, whilst-, and post- teaching so that it is expected that this article give practical benefit to EYL teachersâ classroom practices. Â